MIMO Microstrip Antenna with Multiple Inputs at 2.4 GHz Frequency for Long Term Evolution (LTE) - Sipahutar, Erwinsyah; Oktrison, Oktrison (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
LTE (Long Term Evolution) is a fourth-generation wireless communication technology that is currently under development, necessitating the use of efficient antennas. This research focuses on the design and realization of a Multiple Input Multiple Output (MIMO) microstrip antenna operating at a frequency of 2.4 GHz, which is essential for LTE applications. The MIMO technique employs multiple antennas on both the transmitter and receiver sides, aiming for a correlation coefficient below 0.2 to enhance communication quality and channel capacity without requiring additional bandwidth. The antenna design was simulated using CST Studio Suite 2019 software, followed by fabrication. The simulation results indicated a return loss of -25.411 dB, a Voltage Standing Wave Ratio (VSWR) of 1.113, a gain of 6.464 dBi, an omnidirectional radiation pattern, and a bandwidth of 20 MHz. Upon fabrication, the measured return loss was -18.071 dB, with a VSWR of 1.285 and an increased bandwidth of 50 MHz. The results demonstrate that the designed antenna meets the necessary specifications for LTE applications, confirming its suitability for practical use in modern wireless communication systems.